Public policies in Ecuador and the struggle against sexual harassment - Espinoza Velasteguí, Nereyda Estefanía; Ruscheinsky, Aloisio (Universidad Hemisferios, 2025)
This research addresses a critical gap by exploring how legislative advancements on sexual harassment in Ecuador can be interpreted as mechanisms of social solidarity and promoters of gender equity. The objective is to develop a theoretical framework based on four key dimensions: contextualization of sexual harassment, relevance of its consequences, demystification of stereotypes, and creation of instruments for cultural and social advocacy. The methodology includes a normative analysis that maps Ecuadorian legislation's progress in addressing this social phenomenon, the implementation of policies and protocols as prevention tools, and a rigorous literature review incorporating empirical data to highlight the social issue in Ecuador. The findings emphasize the need to strengthen access to justice, raise societal awareness, and address gaps in the enforcement of laws. We conclude that law creation is a fundamental part of the social process to mitigate this phenomenon. Despite weaknesses in the judicial system, the criminalization of sexual harassment and the establishment of reporting mechanisms contribute to reducing violence against women. The article's implications underscore the crucial role of laws in transforming social relations and promoting sustainable gender equity within the Ecuadorian context.